Correlation between Organizational Learning and Accreditation of Educational Care Centers: A Case Study in Ardabil - Hamed Zandian; Yalda Chamanian; Telma Zahirian Moghadam; Esmaeil Farzaneh (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Considering the importance of organizational learning and its impact on health accreditation, the present study investigates the level of learning and its relationship with accreditation and its promotion strategies in medical sciences universities as the core of the health sector. Methods: In this descriptive-analytic study, data was gathered from 176 nurses working in four teaching hospitals in Ardabil. The standard organizational learning questionnaire and the accreditation rating checklist (second generation) were used as well. Data were analyzed by ANOVA, SPSS22, follow-up tests and correlation coefficient. Results: The results showed that there was no significant difference in the total score of accreditation between teaching hospitals (P-value = 0.320, F = 1.178), but there was a significant difference in organizational learning (P-value > 0.001, F = 146.9) due to the very low rating of one of the centers. The results also showed a positive, significant and strong relationship between the organizational learning score and the total score of accreditation in 4 teaching hospitals in Ardabil (r = 0.319, P-value < 0.001). Conclusion: Based on the results there is a positive and significant relationship between the organizational learning and the accreditation scores. By increasing personnel organizational learning, the accreditation score has also significantly increased. Therefore, with proper policy on organizational learning, educational centers can have a higher level of accreditation in order to provide decent services